Dietary Magnesium Intake and Leukocyte Telomere Attrition in Adults: The Regulatory Role of Serum Tumor Necrosis Factor α - Jie Yu; Haibin Liu; Shuli He; Pingping Li; Chunxiao Ma; Minglei Ma; Yiwen Liu; Lu Lv; Fan Ping; Huabing Zhang; Wei Li; Qi Sun; et al. (Mediators of Inflammation)
Objectives. In this study, we assessed the effects of dietary magnesium on leukocyte telomere length (LTL). Designs. The current cross-sectional analysis was based on data collected within a type 2 diabetes project. Settings. Dietary magnesium intake is associated with peripheral blood leukocyte telomere length (LTL). However, few epidemiological studies have evaluated the effects of magnesium on LTL in the clinical setting. Participants. This cross-sectional analysis included 467 participants (34.8% men). Measurements. Serum blood lipid profile, HbA1c, oxidative stress, and proinflammatory mediator levels were measured. Detailed dietary data were obtained using a 24 h food recall. LTL was assessed using a real-time PCR assay. Regression models and simple regulatory models were used for data analysis. Results. There was an inverse relationship between dietary magnesium and LTL (P<0.001), with a between-extreme-quarter difference of -0.55. Conversely, there was a positive relationship between dietary magnesium and serum tumor necrosis factor (TNF) α, with an interquarter difference of 3.79 pmol/mL (P for trend=0.006). Multivariate regression analysis revealed that the odds ratios (ORs) for shorter LTL and higher serum TNFα increased with magnesium intake, and the ORs of the differences between extreme quartiles were 2.60 (95% confidence interval (CI): 1.31–5.36; P=0.003) and 1.98 (95% CI: 1.09–3.59; P=0.008). There was a direct negative effect of dietary magnesium intake on LTL (B=−0.002; P=0.001), which appeared to be indirectly influenced by TNFα (-0.002 to -0.0005). Conclusions. Dietary magnesium intake may be a critical component of the cellular aging process, and its effect could be partly mediated by TNFα.